P.093 Thorascopic assisted resection of dumbbell nerve sheath tumors. (2nd June 2017) - Sharma, S; Power, R; Reddy, K
Abstract : Background: Surgery to remove dumbbell nerve sheath tumors (NST) is complex, and is accompanied by significant operative and perioperative challenges. Historically, resection of dumbbell NST required large operations involving opening the chest and laminectomy, often accompanied by instrumentation. We describe a case series of 5 patients who underwent single stage thorascopic-guided resection of dumbbell schwannoma at our institution.Methods: 5 cases presented consisted of moderate to large NST, which contained intraforaminal components. Tumor location ranged from T3-T9, with most tumors spanning 2-3 vertebral bodies. Presentation ranged from discomfort/pain (most common) to one presentation of neurologic deficit with difficulty with ambulation.Results: Thorascopic assisted resection accomplished gross total resection in 4 of the 5 cases. In all cases there was no significant neurologic deficit, although one patient reported transient numbness following the operation and all patients made significant improvement post operatively. The length of stay for these cases ranged from 1-6 days.Conclusions: Thorascopic assisted resection of dumbbell NST can be performed safely and with good outcomes by using the corridor the tumor produces. This approach reduces the need for instrumentation, length of stay and post operative complication rates relative to traditional approaches. To perform this approach effectively, good co-operation between the neurosurgeon and thoracic surgeon needs to be present.